Molecular and biological Study of Colibacillosis Susceptibility in broiler - Hassan Zaher; Balqees Hassan Ali (University of Thi-Qar Journal of agricultural research, 2023)
This study was aimed to Detection of virulence genes(rfbE) It was carried in College of Veterinary Medicine at Baghdad university, During a time span of November (2021) to March (2022). (100) samples were collected from diarrheal chicken . 100 chicks were used in the present study, One day old chicks were weighed (Average of chick weight was 160 gm±2) then transferred to the poultry house. Chicks in wards that were divided by wood barriers. Diagnosis of bacterial colonies were first done by the bacteriological methods. From (100) fecal samples of diarrheal cases of chicken , 90(90%) isolates were Escherichia coli.In the present study using vitek 2 compact system and Api 20 Escherichia coli. for the identification isolated bacteria. PCR technique was used to Detection of virulence genes(rfbE) ,The result for rfbE gene in this study was showed that this gene was detected in(60) isolates of (90) samples of chicken observed carried the rfbE gene which represent (67%).